Gas chromatography analysis for the performance evaluation of the palm oil cross-metathesis using 1-octene - Thangavel, Mythili; Chin, Sim Yee (School of Renewable Energy, Maejo University, 2021)
alm oil is one of the important raw materials in the oleochemical industry for downstream expansion and sustainability. The built-in functionality and availability of oil worldwide make palm oil more attractive. It can be further modified using the cross-metathesis process for the production of bio-based polyol. In this study the cross metathesised palm oil was pre-treated with different types of pre-treatment methods namely transesterification, silylation, methylation and dilution to find the best pre-treatment method. Moreover, the pre-treated samples were analysed using two different Gas chromatography columns installed to the Gas chromatography flame ionisation detector (GC-FID). The best pre-treatment method was then used to prepare the samples taken from the palm oil octenolysis at different molar ratio of palm oil to 1-octene. According to the findings of this research, dilution method outperformed other pre-treatment methods.